Foot waqf scheme of Islamic religious council of Kedah (Maik): case study in district of Kota Setar - Azhar, Alias (Universiti Malaysia Perlis, 2017)
Waqf institution plays a role as a catalyst in improving the socio-economic status of the Muslim community. Recognizing this fact, Islamic Religious Council of Kedah (MAIK) has taken innovative initiatives to strengthen this institution by introducing foot waqf scheme. In this regard, this article will discuss the concept of waqf in general and the foot waqf scheme focusing on its implementation in Kota Setar, Kedah. The data obtained from library research, documentation, interviews with stakeholders, site observations and surveys were used as sources for qualitative analysis. The findings show that the foot waqf scheme has succeeded in achieving its goals despite facing some problems and obstacles. Subsequently, several suggestions were raised to overcome this problem from continuing in the future so that waqf of land property could be further developed through a foot waqf scheme and become a valuable asset for the economic growth of Muslims in Kedah